2016
DOI: 10.1155/2016/6716329
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Research on Seismic Performance of Earthquake-Damaged RC Frame Strengthened with CFRP Sheets

Abstract: In order to assess the seismic performance of damaged reinforced concrete (RC) frame strengthened with carbon fiber reinforced polymers (CFRP) sheets, two experimental specimens with identical reinforcement ratio and geometric dimensions were designed following Chinese code for seismic design of buildings. Experimental specimens consist of a reference (undamaged) RC frame, namely, KJ-1, and an earthquake-damaged RC frame strengthened with CFRP sheets, namely, KJ-2. A pseudostatic test was conducted on the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After steel bar yielding, produce large plastic deformation and the strain increase gradually when exert positive load; When apply reverse load, the strain of the reinforced bar is not synchronized with the forward time due to the large residual strain. With the increase of applied load, the adhesion stress between steel bar and concrete decreases and the slip occurs, which leads to the decrease of the strain value of the bar [3] . ﹙4﹚When the forward load is carried out, the measurement points 32 and 41 are in tension state and the tensile strain change is relatively large; When apply reverse load, the test points 36 and 39 are in state of compression and the change of the compressive strain is relatively large.…”
Section: Strain Analysis Of Steel Barmentioning
confidence: 99%
“…After steel bar yielding, produce large plastic deformation and the strain increase gradually when exert positive load; When apply reverse load, the strain of the reinforced bar is not synchronized with the forward time due to the large residual strain. With the increase of applied load, the adhesion stress between steel bar and concrete decreases and the slip occurs, which leads to the decrease of the strain value of the bar [3] . ﹙4﹚When the forward load is carried out, the measurement points 32 and 41 are in tension state and the tensile strain change is relatively large; When apply reverse load, the test points 36 and 39 are in state of compression and the change of the compressive strain is relatively large.…”
Section: Strain Analysis Of Steel Barmentioning
confidence: 99%
“…Mahdavi et al [18] proposed the optimise design procedure (algorithm) of the seismically retrofitting reinforced concrete structures based on the stress-strain relationship of square column cross section with FRP. Some studies also consider rectangular cross sections [19][20][21][22][23][24]. Lam and Teng [19] and Ouyang and Liu [20] proposed a stress-strain model for the FRP-confined concrete of the rectangular columns.…”
Section: Introductionmentioning
confidence: 99%
“…Lam and Teng [19] and Ouyang and Liu [20] proposed a stress-strain model for the FRP-confined concrete of the rectangular columns. Wang et al [22] presented the analysis models of the reinforced concrete frame (rectangular cross section) strengthened with carbon fiber-reinforced polymer (CFRP) sheets. However, the ratio of the long to short side (longitudinal ratio) on these studies is around 2, and wall members are beyond their scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…Beydokhty and Shariatmadar (2016) strengthened eight damaged external beam–column joints with external CFRP sheets, in which the result revealed that the CFRP is effective in restoring load capacity and stiffness of damaged joints. Wang et al (2016) applied exterior CFRP sheet on damaged RC frame and carried out experimental and numerical tests. The results revealed that bearing capacity, stiffness, and ductility of the RC frame were restored to its original undamaged level.…”
Section: Introductionmentioning
confidence: 99%